KEANEKARAGAMAN BAKTERI PENGHASIL EKSOPOLISAKARIDA ASAL SALURAN CERNA MANUSIA - Achmad Dinoto; Sugiyono Saputra; Agustinus Joko Nugroho; Rita Dwi Rahayu (The East Java Biological Society, 2011)
Exopolysaccharide (EPS) is a polysaccharide that is excreted by cell as metabolites. Bacterial EPS has been widely used in food and drug industries. In order to find natural products for foods and drugs, the study was conducted to know the diversity of EPS-producing bacteria isolated from human gastrointestinal tracts. As much of 30 bacterial strains were collected from two healthy people and seventeen of collected isolates were investigated for the capability of producing EPS. As the results of identification by partial 16S ribosomal DNA analysis, those seventeen EPS-producing bacterial strains were closely related with already known bacteria (range between 86 to 100% similarity) and could be classified into seven genus, i.e.: Lactobacillus spp. (9 strains), Enterobacter sp. (2 strains), Escherichia sp. (2 strains), Klebsiella sp. (1 strain), Cronobacter sp. (1 strain), Staphylococcus sp. (1 strain), and Alteromonas sp. (1 strain). In addition, member of Lactobacillus group which have closest relationship with species L. plantarum (7 strains) dan L. fermentum (2 strains) were known to dominate the collection of culturable EPS-producing bacteria from human gastrointestinal tracts.